The Effectiveness of Problem Based Learning on Acid-Base Materials to Improve Scientific Attitude and Creativity of SMA N 1 Comal Students - Dirmanto, Agus; Cahyono, Edy; Sulistyaningsih, Triastuti (Universitas Negeri Semarang)
The learning model is fundamental to increase the effectiveness of the teaching and learning process in the classroom. Learning models that make students more active in the chemistry teaching and learning process in class XI SMA N 1 Comal are rarely used. As a result, students become passive and scientific attitudes and student creativity have not developed. This study aims to determine : the process of implementing problem-based learning (PBL), the effectiveness of PBL on acid-base material in high school, increasing the scientific attitude and creativity of class XI SMA students. The research design used was a pretest-postest control group with a quasi experimental design. This study’s population was all students of class XI SMA N 1 Comal in the academic year 2020/2021. The sample was taken using simple random sampling technique and selected class XI MIPA 5 as the control class and XI MIPA 6 as the experimental class. Data collection techniques used documentation in the form of pretest and postest scores, scientific attitude observation sheets and questionnaires to measure student creativity. The data analysis technique used is the t-test. The results showed that the average posttest score of students in the experimental class were higher than the average posttest score of students in the control class. The percentage of students with a high scientific attitude in the experimental class is also more remarkable than the control class. The creativity category with a very creative category in the experimental class shows a more significant percentage than the control class. From the analysis results, it can be concluded that first, the application of PBL starts from problem orientation, group organizing, conducting experiments, presenting work results, and evaluating. The second is the problem based learning model provides excellent results and is quite effective compared to conventional methods. Third, PBL models can improve student’s scientific attitudes and creativity compared to conventional methods.